Phylogenomics and plastome evolution of Indigofera (Fabaceae) - Zhou, Sheng-Mao; Wang, Fang; Yan, Si-Yuan; Zhu, Zhang-Ming; Gao, Xin-Fen; Zhao, Xue-Li (Frontiers in Plant Science, 2023)
Indigofera L. is the third largest genus in Fabaceae and is comprised of economically important species that are used for indigo dye-producing, medicinal, ornamental, and ecological conservation plants. The genus is taxonomically difficult due to the high level of morphological diversity and extensive adaptive evolution. Previous characteristic-based taxonomy and nuclear ITS-based phylogenies have contributed to our understanding of Indigofera taxonomy and evolution. However, the lack of chloroplast genomic resources limits our comprehensive understanding of the phylogenetic relationships and evolutionary processes of Indigofera. Here, we newly assembled 18 chloroplast genomes of Indigofera. We performed a series of analyses regarding genome structure, nucleotide diversity, phylogenetic analysis, species pairwise Ka/Ks ratios, and positive selection analysis by combining using allied species in Papilionoideae. The chloroplast genomes of Indigofera exhibited highly conserved structures and ranged in size from 157,918 to 160,040 bp, containing 83 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Thirteen highly variable regions were identified, of which trnK-rbcL, ndhF-trnL, and ycf1 were considered as candidate DNA barcodes for species identification of Indigofera. Phylogenetic analysis using maximum likelihood (ML) and Bayesian inference (BI) methods based on complete chloroplast genome and protein-coding genes (PCGs) generated a well-resolved phylogeny of Indigofera and allied species. Indigofera monophyly was strongly supported, and four monophyletic lineages (i.e., the Pantropical, East Asia, Tethyan, and Palaeotropical clades) were resolved within the genus. The species pairwise Ka/Ks ratios showed values lower than 1, and 13 genes with significant posterior probabilities for codon sites were identified in the positive selection analysis using the branch-site model, eight of which were associated with photosynthesis. Positive selection of accD suggested that Indigofera species have experienced adaptive evolution to selection pressures imposed by their herbivores and pathogens. Our study provided insight into the structural variation of chloroplast genomes, phylogenetic relationships, and adaptive evolution in Indigofera. These results will facilitate future studies on species identification, interspecific and intraspecific delimitation, adaptive evolution, and the phylogenetic relationships of the genus Indigofera.